Tzaiad Ha'Natzim Ha'hacharon - Goven, Nitza (Israel, 2012)
70 years after the Holocaust, American born-Israeli Dr. Efraim Zuroff is tracking down surviving Nazi war criminals in hopes to bring them to justice. Zuroff's mission takes him all over Europe and even South America as he and locates two main criminals; Sandor Kapiro, a Hungarian officer responsible for the murder of thousands of Jews, and Dutch Waffen SS Klass Faber, who oversaw the killings at the Westerbork Camp.
Verzio Film Festival Submission
Verzio Film Festival Submission
Keywords: Documentary films